Usaha Mebel Yumna Sofa di Desa Padang Mekar Kecamatan Padangguni Kabupaten Konawe - Leni Saleh; Riana Nur Fadilla; Rian Andika Putra; Nuryanti Nuryanti; Juliana Eka Putry; Nasmuddin Nasmuddin (FKIP, Universitas Palangka Raya, 2024)
This community service (PKM) uses a participatory approach from partners (participatory approach) so that partners are involved starting from identifying problems, selecting solutions. The